The The Role of Sharia Financial Institutions in Fighting Poverty in Jayapura: lembaga keuangan syariah, kemiskinan, inklusi keuangan, pemberdayaan ekonomi, Jayapura - Hasyim, Khoiriya; Putri, Putri; Hikmah, Nur; Hanifah, Nani (Jurnal Istiqro, 2025)
In the context of the role of Islamic Financial Institutions in combating poverty in Jayapura, it is important to understand how Islamic financial institutions can be a solution to address the complex problem of poverty. With Islamic sharia principles that are different from conventional financial institutions, Islamic Financial Institutions (LKS) are able to provide inclusive and sustainable financial services to the community. Through fundraising, fund distribution, asset transfer, liquidity, income allocation, and transactions based on sharia principles, LKS can make a positive contribution to improving the welfare of the Jayapura community. With cooperation between Islamic financial institutions, the government, and the community, it is hoped that efforts to combat poverty can continue to be improved to achieve inclusive and sustainable development in the city of Jayapura. Poverty is a serious challenge faced by many communities in Jayapura, Indonesia. Islamic financial institutions have great potential to contribute to combating poverty through an inclusive economic approach based on sharia principles. This study aims to explore and analyze the role of Islamic financial institutions in poverty alleviation efforts in Jayapura. This study uses a qualitative approach by conducting in-depth interviews and document analysis of several major Islamic financial institutions in Jayapura. The research results show that Islamic financial institutions have made a significant contribution to increasing financial access for previously marginalized communities, especially through micro and small financing and local economic empowerment programs.